Assessment of Chaves Low-Temperature CO2-Rich Geothermal System (N-Portugal) Using an Interdisciplinary Geosciences Approach - J. M. Marques; P. M. Carreira; L. A. Aires-Barros; F. A. Monteiro Santos; M. Antunes da Silva; P. Represas (Geofluids)
This paper reviews the results of a multi- and interdisciplinary approach, including geological, geomorphological, tectonic, geochemical, isotopic, and geophysical studies, on the assessment of a Chaves low-temperature (77°C) CO2-rich geothermal system, occurring in the northern part of the Portuguese mainland. This low-temperature geothermal system is ascribed to an important NNE-trending fault, and the geomorphology is dominated by the “Chaves Depression,” a graben whose axis is oriented NNE-SSW. The study region is situated in the tectonic unit of the Middle Galicia/Trás-os-Montes subzone of the Central Iberian Zone of the Hesperic Massif comprising mainly Variscan granites and Paleozoic metasediments. Chaves low-temperature CO2-rich geothermal waters belong to the Na-HCO3-CO2-rich-type waters, with pH≈7. Total dissolved solids range between 1600 and 1850 mg/L. Free CO2 is of about 500 mg/L. The results of SiO2 and K2/Mg geothermometers give estimations of reservoir temperature around 120°C. δ18O and δ2H values of Chaves low-temperature CO2-rich geothermal waters indicate a meteoric origin for these waters. No significant 18O-shift was observed, consistent with the results from the chemical geothermometry. δ13CCO2 values vary between −7.2 and −5.1‰ vs. V-PDB, and CO2/3He ratios range from 1×108 to 1×109, indicating a deep (upper mantle) source for the CO2. 3He/4He ratios are of about 0.9 (R/Ra). The Chaves low-temperature CO2-rich geothermal waters present similar 87Sr/86Sr ratios (between 0.728035 and 0.716713) to those of the plagioclases from granitic rocks (between 0.72087 and 0.71261) suggesting that water mineralization is strongly ascribed to Na-plagioclase hydrolysis. Geophysical methods (e.g., resistivity and AMT soundings) detected conductive zones concentrated in the central part of the Chaves graben as a result of temperature combined with the salinity of the Chaves low-temperature CO2-rich geothermal waters in fractured and permeable rock formations. This paper demonstrates the added value of an integrated and multi- and interdisciplinary approach for a given geothermal site characterization, which could be useful for other case studies linking the assessment of low-temperature CO2-rich geothermal waters and cold CO2-rich mineral waters emerging in a same region.